Influence of a Lashing Strap Winding in Tensioning Ratchet on the Results of the Strength Tests and Cyclic Loading Tests According to the Standard EN 12 195-2 - Jan Zamecnik; Juraj Jagelcak; Sven Sokjer-Peterssen; Tomas Hvojnik; Michal Lipka (Communications - Scientific letters of the University of Zilina, 2017)
This article is focused on the results of the testing of the complete web lashing and the cyclic loading tests of selected lashing straps of three various producers according to the standard EN 12 195-2. It analyses how the quantity of winding in tensioning ratchet affects the results of these tests, whereas it compares the results of the straps wound 2¼ times around the rotating axis (as is correct according to the standard) and those wound 1¼ times around the rotating axis (as is not enough quantity of a winding). The article concludes that the influence of the winding on elongation of straps as well as on operating life of the straps is strong. Damages on particular parts of complete lashing straps, which were found out within these tests, are also presented in the article.